The Value of Endoscopic Decompression in Surgical Therapy of Carpal Tunnel Syndrome - Hessenauer, Maximilian E. T.; Arkudas, Andreas; Ludoph, Ingo; Polykandriotis, Elias; Horch, Raymund E. (Zentralblatt für Chirurgie, 2018)
Carpal tunnel syndrome is one of the most common diseases in hand surgery. The gold standard in therapy is the surgical release of the carpal tunnel. We provide a brief update on the relevant pathogenesis, diagnosis and therapy and discuss questions related to minimal invasive decompression of the median nerve. Together with a review of the current literature, we report on our experiences in minimally invasive carpal tunnel release via a monoportal endoscopic access in over 700 cases. In conclusion, the endoscopic technique provides superior convalescence and patient safety is comparable to open methods. In addition, advantages and disadvantages of the various techniques are discussed.
EVALuna2:211482